ANALISIS HUTAN KOTA METRO BERDASARKAN KEANEKARAGAMAN JENIS POHON - Panjaitan, Bernad Uluan; Indriyanto; Asmarahman, Ceng (Jurusan Kehutanan, 2021)
The diversity of tree species in urban forests has benefits in maintaining the microclimate, aesthetic value, and preserving biodiversity in the urban environment. This study aims to analyze the diversity of tree species in the Metro City Forest. Data collection on the diversity of tree species was taken using purposive sampling method. Tree species diversity data were analyzed using the significance value index (INP) and the Shannon diversity index (H). The results showed that the mahogany species had the highest INP value, which was 52.7%. The Tesarigaga City Forest has the highest diversity index value of 2.38 which is included in the medium category and the Islamic Center City Forest has the lowest diversity index value of 1.27 which is included in the low category. This can be increased through tree diversity by increasing the diversity of plant species as a source of germplasm.